AIR KEMIH (URIN) BEREOSINOFIL DENGAN DUGAAN RADANG SELA GINJAL MENDADAK/NEFRITIS INTERSTISIAL AKUT (NIA) - Felly G Sahureka; Fitriani Mangarengi; Uleng Bahrun (Indonesian Association of Clinical Pathologist and Medical laboratory, 2010)
The diagnosis of AIN is performed by the evaluation of clinical signs and symptoms, laboratory tests, radio imaging and biopsyas a gold standard. In most cases, biopsy wasn't performed because it is invasive for the patients, while the diagnosis is just based onthe clinical sign and symptom, and the immunosuppressive therapy is carried out only after the biopsy. Eosinophyluria found in theAIN patients is the parameter that can be measured non invasively, so that urine eosinophyl test was suggested for the diagnosis/earlydetection of AIN. That background cause us to analyze the urine eosinophyl count in suspected AIN patients. A cross sectional studywas conducted from June to August 2008 on 50 suspect AIN patients and 50 of non AIN at the Laboratory of Clinical Pathology,dr.Wahidin Sudirohusodo Hospital Makassar. Urine eosinophyl test performed by Hansel method, samples were analyzed with SPSSfor Windows version 12.0 using T test and Chi-square test. From 50 suspect AIN patients, they consist of 50% men and 50% womenwith the age distribution between 4 and 72 years old. T test analysis showed that the urine eosinophyl count was higher in suspect AIN(2.820 ± 1.955) compare with the non AIN (0.620 ± 0.923), p < 0.001. The Chi-square test showed that there was a significantrelation between eosinophyluria of the suspect AIN patients. That means there is a significantly relation between eosinphyiluria withthe suspect AIN group, where was found the higher urine eosinophyl compare to those non AIN patients. From this study so far, it canbe suggested that urine eosinophyl test can be used for the diagnosis/early detection of AIN.